Dislocation Density-Based Finite Element Models for Viscoplasticity and Creep of High-Temperature Materials - Al-Abedy, Hiydar Kireem Musraa (2020)
High strength materials that are used in modern power generation plants have now received much more attention because of being exposed to significant thermal gradients due to the fluctuation of demand in daily operation. However, the nature of these materials is complex and several aspects of the evolution of the microstructure still need investigation. Thus, time-dependent plasticity and creep models are appropriate for modelling the P91 steel behaviour under thermomechanical loading. This thesis reports the findings of finite element (FE) analyses and experimental investigations of uniaxial tensile, conventional creep, small punch creep (SPCT) and small tensile test (SPTT) carried out with objective of enhancing the understanding of various microstructural features which describe the creep and viscoplastic behaviours of the specimen. It also aims to develop macro-scale material models, which can predict the creep and viscoplastic behaviours under high-temperature conditions, based on microstructural variables including dislocation density and various other parameters which specify the material structure. A creep model was developed based on the initial microstructural variables of dislocation density at high-temperature conditions. This model is used to simulate the small punch creep behaviour of the P91 steel at 600°C. Finite element simulations of a small punch creep tests are carried out using ABAQUS software coupled with a UMAT material subroutine. The effect of friction behaviour of the contact between punch and specimen was investigated for SPCTs for a range of levels of applied stress. The FE results observed that could utilize the microstructure properties to predict the creep behaviour for P91 steel at elevated temperatures. A unified, Kocks-Mecking-Estrin (KME), viscoplasticity model, which includes isotropic hardening with a viscoplastic flow rule for time-dependent effects by growth and annihilation of dislocations, was used to model the uniaxial tensile and conventional creep behaviour of P91 steel at 600℃. This model was also used in the finite element simulations using a UMAT subroutine within the ABAQUS software. The prediction of the model was improved by including the nonlinear isotropic hardening in order to obtain better stress-strain behaviour in the necking and fracture phase. The prediction of necking and fracture shows good agreement in comparison with experimental testing. The results also show that flow stress at elevated temperatures can be well-characterized by the KME model with the dislocation hardening term. The experimental tests on all specimens in the study were performed using the Tinius Olsen H5KS single column material testing machine with loading accuracy of ± 0.5% of the applied load within isothermal conditions of 600℃. The small punch tensile behaviour of the P91 steel was further studied by analysing data for force vs. punch displacement at 600°C and by performing microstructural investigations. Physical characterisation of the deformed specimens was conducted via scanning electron microscopy (SEM), coupled with energy dispersive X-ray spectroscopy (EDS), and electron backscatter diffraction (EBSD) to investigate bulk deformation, microstructural evolution, grain structure change and the crack initiation of the P91 at different stages within all tests. The results show that the bulk deformation behaviour during SPTT indicates to six deformation reigns. The evolution of microstructure occurs after maximum load due to void nucleation resulting in significant necking and thinning at the edge of contact between specimen and punch. The grains exhibit elongation along plastic flow direction. A visco-plastic model is then developed, based on the microstructural variables of dislocation density, PAGs size and martensitic lath width at high temperature conditions. The developed model was also used in the finite element simulations using the ABAQUS software coupled with a UMAT material subroutine. The finite element simulation was used to validate the performance of the model under multiaxial stress states. FE simulation results were compared with the isothermal small punch tensile tests data of the P91 steel at 600℃. The results of the FE simulation showed that the friction coefficient varies over the contact surface between punch and specimen, and this impacts on the small punch tensile results. The results of FE simulation also showed that the initial of micro-structural variables play an influential role on the small punch tensile results. Dislocation densities, the PAGs size and lath martensitic width and the friction coefficient can interact and have a strong effect on the macroscopic degradation of the material at high stress and elevated temperature conditions. The obtained results have also shown the model’s versatility and good predictive capabilities for representing the viscoplastic behaviours of the P91 steel at 600 °C.